Strategies For Maintaining Quran Memory Through Holiday Classes Management A Case Study At The Muslim Cendekia Institute In Sukabumi - Resi Hanifah; Hadil Ismail Hasan (EDUJAVARE: International Journal of Educational Research, 2026)
This research aims to describe the management of the Holiday Halaqah program at Institut Muslim Cendekia (IMC) Sukabumi in maintaining students' memorization quality (itqan) during the academic holiday period. Holidays are often a critical period where students lose their memorization rhythm, necessitating specific management strategies to mitigate this risk. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews with 13 informants, participatory observation, and documentation studies, then analyzed using the Miles, Huberman, and Saldaña model. The results indicate that IMC Sukabumi implements four management functions integratively: 1) Planning with differentiated memorization cluster targets; 2) Organizing through a peer-tutoring system by "Musyrifat" with a 1:10 ratio; 3) Actuating through a "Positive Isolation" method that combines intensive tikrar methods with various recreational-educational activities to prevent burnout; and 4) Controlling through mutaba'ah records, memorization competitions, and final examinations (ikhtibar). Final exam results for 79 students showed an exceptionally high success rate of 96.2%, with 68.3% of students achieving excellent scores (90-100). The study concludes that the centralized management of the halaqah program in the dormitory during the holiday period is effective in strengthening students' itqan and preparing their academic readiness for the upcoming academic year